Identification of a tumor suppressor network in T-cell leukemia. Issue 9 (2nd September 2017) - Nagel, Stefan; Pommerenke, Claudia; Meyer, Corinna; Kaufmann, Maren; MacLeod, Roderick A. F.; Drexler, Hans G.
Abstract: To identify novel cancer-related genes targeted by copy number alterations, we performed genomic profiling of T-cell acute lymphoblastic leukemia (T-ALL) cell lines. In 3/8, we identified a shared deletion at chromosomal position 2p16.3-p21. Within the minimally deleted region, we recognized several candidate tumor suppressor (TS) genes, including FBXO11 and FOXN2. An additional deletion at chromosome 14q23.2-q32.11 included FOXN3, highlighting this class of FOX genes as potential TS. Quantitative expression analyses of FBXO11, FOXN2, and FOXN3 confirmed reduced transcript levels in the identified cell lines. Moreover, reduced expression of these genes was also observed in about 7% of T-ALL patients, showing their clinical relevance in this malignancy. Bioinformatic analyses revealed concurrent reduction of FOXN2 and/or FOXN3 together with homeobox gene ZHX1. Consistently, experiments demonstrated that both FOXN2 and FOXN3 directly activated transcription of ZHX1. Taken together, we identified novel TS genes forming a regulatory network in T-cell development and leukemogenesis.